Soot morphology and nanostructure in complex flame flow patterns via secondary particle surface growth. (1st June 2019) - Davis, Justin; Tiwari, Kartik; Novosselov, Igor
Highlights: Fluid recirculation significantly increases primary particle diameter. Recirculating and non-recirculating flames both display shell-core nanostructure. Recirculating soot has both single core and multiple core primary particles. Proposed secondary soot growth mechanism in flames with complex flow patterns. Abstract: While the majority of studies explore soot formation in relatively simple, one-dimensional flames, most real-world flames consist of complex flows defined by large-scale turbulent eddies, recirculating flow patterns, and buoyancy effects. The effects of complex flow on soot physicochemical properties are poorly understood. This work employs an inverted gravity flame reactor (IGFR) to compare differences in soot growth between a one-dimensional laminar diffusion flame and a recirculating flame. Computational fluid dynamics (CFD) and experimental observations show particle oscillations between (i) a rich region with a high concentration of surface growth species, and (ii) a high-temperature oxidation region. Transmission electron microscopy (TEM) shows a significant difference in final primary particle diameter, where the one-dimensional flame produces primary particles 10–25 nm in diameter and the recirculating flame produces primary particles 25–75 nm in diameter. Additionally, larger primary particles from the recirculating flame contain both single and multiple cores. We propose that due to the spheroidal shape of the large primary particles, the secondary surface growth is primarily a result of polyaromatic hydrocarbon (PAH) condensation during re-entrainment of mature soot into the fuel-rich region followed by subsequent liquid layer carbonization in the high-temperature environment of the flame front. The recirculating flow patterns in the IGFR and repeated particle growth/oxidation cycle can serve as a model for soot formation in the large-scale flames with complex flow patterns, such as forest fires, coal fire plants, and other sources.